Implementasi Jaringan VPN Site-to-Site dan Protocol OSPF Menggunakan Cisco di Sekolah Bina Bangsa - Prayitno, Hadi; Sobari, Irwan Agus (Universitas Lampung, 2025)
The development of technology is currently very rapid. The need for information is critical, especially in work, this need continues to grow along with users who want fast, safe, and efficient information. Sekolah Bina Bangsa is not directly connected to the network so it is very vulnerable to data leaks and can be considered less secure, so it is necessary to implement VPN (Virtual Private Network) technology. With VPN (Virtual Private Network), data delivery can be more secure because of the encryption method provided by this VPN technology. The OSPF (Open Shortest Path First) protocol is a technology that is applied to help reduce bandwidth in network usage because this protocol can determine the best path in choosing a network route, so it is expected to reduce the existing bandwidth. To prevent foreign devices that are not registered in the network system at school, the author proposes the implementation of Switch-port Security with a violation shutdown configuration. With this configuration, if a foreign device accesses the school network, it will automatically be shut down. Thus, by implementing the existing network system at Bina Bangsa School, it is hoped that data transmission between the Kebon Jeruk Campus and PIK can be carried out safely, can reduce bandwidth in the network, and also the internal network cannot be accessed carelessly by outsiders who are not registered in the network system at Bina Bangsa School.